Religion as a practical relation of recognition in Hegel’s phenomenology of the spirit - Nación Pantigoso, Miguel Ángel (2021)
This article seeks to understand the role that religion plays in Hegel, specially, in his work Phenomenology of the Spirit, taking the concept of recognition as the hermeneutical key of the Hegelian work. For this, we first historically locate the appearance and reception of the concept of recognition in German Idealism. Then, we present the structure of reconciliation relationships between subject and object that Phenomenology supposes. We conclude by highlighting the role that religion has as a category of self-awareness in the structure of recognition relationships inmodern society.